Delivery room resuscitation and short-term outcomes in very preterm infants: a multicenter cross-sectional study in China - Lin, Hanni; Yu, Zhangbin; Huang, Jinjie; Yang, Ting; Duan, Shitao; Guo, Yanping; Zeng, Shujuan; Jiang, Ping; Wang, Rui; Zhang, Jing; Ding, Lu; Liu, Jiebo (Frontiers in Pediatrics, 2024)
Objective: To explore the risk factors of delivery room (DR) resuscitation and assess the association of DR resuscitation with neonatal outcomes in very preterm infants (VPIs).Methods: A multicenter retrospective cross-sectional study included VPIs with gestational age (GA) <32 weeks born between January, 2022 and June, 2023 and admitted to neonatal intensive care units of six tertiary hospitals in Shenzhen within 24 hours after birth. They were divided into routine care group, positive-pressure ventilation (PPV) group, and endotracheal intubation (ETT) group based on the highest intensity of resuscitation received at birth. The association of antepartum and intrapartum risk factors and short-term outcomes with the intensity of DR resuscitation was evaluated.Results: Of 683 infants included in this study, 170 (24.9%) received routine care, 260 (38.1%) received bag and mask ventilation or T-piece ventilation and 253 (37%) received ETT.Among the antepartum and intrapartum factors, exposure to antenatal steroids (ANS) decreased the likelihood of ETT. Increasing GA decreased the likelihood of receiving a higher level of DR resuscitation. Among the neonatal outcomes, increasing intensity of DR resuscitation was associated with a raise in the risk of Bronchopulmonary dysplasia. Higher levels of DR resuscitation were associated with the risk of early-onset sepsis. ETT was significantly associated with an increased risk of death.Among VPIs, low GA and no ANS use increased the risk of high-intensity DR resuscitation interventions; and those who receiving ETT were associated with an increased risk of adverse clinical outcomes.